A Walk on the Wild Side: 2019 Cool-Season Forage Recommendations for Wildlife Food Plots in North Florida - Ann R. Blount; Marcelo Wallau; Holly K. Ober; Esteban Rios; Joao M. B. Vendramini; Jose C. B. Dubeux; Md A. Babar; Cheryl L. Mackowiak; Kenneth H. Quesenberry (EDIS)
This 5-page minor revision brings an updated list of recommended species and cultivars for the establishment of wildlife plots in Florida. Written by A. R. Blount, M. Wallau, H. K. Ober, E. Rios, J. M. B. Vendramini, J. C. B. Dubeux, Md. A. Babar, C. L. Mackowiak, and K. H. Quesenberry, and published by the Agronomy Department, October 2019.